MOLECULAR DOCKING AND ADMET STUDIES OF BENZOTRIAZOLE DERIVATIVES TETHERED WITH ISONIAZID FOR ANTIFUNGAL ACTIVITY - AISWARIYA; B. V., SUMA; SATYA, MEDICHARLA SRI (International Journal of Current Pharmaceutical Research, 2022)
Objective: The incidence of fungal infections is increasing at an alarming rate, presenting an enoromous challenge to health care professionals. This increase is directly related to the growing population of the immunocompromised individuals, resulting from changes in the medical practice such as the use of intensive chemotherapy and immunosuppressive drugs. The ability of many fungi to form biofilms is one of the reasons for the antifungal resistance caused and hence there is an urgent need in the synthesis of new and safer anti-microbial agnets. Benzotriazole is an organic heterocyclic compound with 2 nitrogen atoms in the ring having wide range of biological properties like anti-tubercular, anticancer and anti-microbial etc. isoniazid is the first line drug used to treat tuberculosis. Tethering benzotriazole with isoniazid has shown development of newer compounds that may exhibit better activity on inhibiting the fungal growth and replication and hence has shown a positive effect on the anti-fungal activity. Methods: Affinity between the protein and ligand was found out using rigid docking technique.3D structure of the fungal protein was downloaded from protein data base. The selected ligand molecules are generated using Chem Draw. ADMET studies for the molecules are determined using SWISS-ADMET website. Rigid docking is employed to find the binding affinities between ligand and protein. Results: 4 derivatives of benzotriazole tethered with isoniazid were selected and docking studies were carried out for these compounds with the antifungal protein,14 alfa-demethylase with PDB I. D; 5V5Z,using molecular docking tool PyRx and docking scores were-8.3,-7.6,-9.2,-7.4 respectively when compared with the standard compound Fluconazole (-8.0). ADMET studies of the 4 compounds have shown zero violation to lipinski’s rule. Conclusion: In summary, benzotriazole derivatives tethered with isoniazid exhibits promising results based on in silico studies. ADMET studies showed that the compounds drug likeness parameters are according to lipinski’s rule of five.